Potencial gastroprotetor e cicatrizante de galactomanana extraída das sementes de Adenanthera pavonina Linn. - MARTINS , Erika Meire dos Santos (2019)
Peptic ulcer disease (DUP) refers to lesions in the mucosa of the stomach or duodenum and its main drug treatment aims to decrease the secretion of gastric acid and is usually associated with the eradication of H. pylori bacteria. The seeds of Adenanthera pavonina Linn are characterized as a typical source of endosperm gums, commonly known as galactomannans. The objective of this work was to investigate the gastroprotective and cicatrizing potential of galactomannan extracted from the seeds of Adenanthera pavonina in rats. Initially, galactomannan extraction from Adenanthera pavonina seeds and galactomannan centesimal analysis were performed for moisture, protein, lipids, ashes and carbohydrates. Gastroprotective activity was assessed using the acute ethanol-induced gastric injury model in rats previously treated for 15 days prior to induction of the lesion. Absolute ethanol lesions were submitted to in vivo antioxidant activity analysis for quantification of sulfhydryl groups and levels of lipid peroxidation and histological analysis. The cicatrizing action was evaluated using the chronic ulcer model induced by acetic acid. The effect of Adenanthera pavonina galactomannan on intestinal transit and gastric emptying was also evaluated. In relation to the centesimal composition of Adenanthera pavonina galactomana, values for moisture of 14.73 ± 0.84%, ashes 0.01%, lipids 2.70 ± 0.47% and total carbohydrates (82.28 ± 0%, 61%), and no proteins were detected in the sample. The previous treatment with Adenanthera pavonina galactomannan for 15 days reduced the formation of gastric mucosa lesions induced by ethanol in 80.19%, when compared to the control group. As for the antioxidant activity in vivo, Adenanthera pavonina galactomannan did not reverse the levels of sulfhydryl groups. However, it was able to generate a significant reduction in the levels of malondialdehyde, that is, it reduced the rate of lipid peroxidation promoted by ethanol in the mucosa. Regarding the histological analysis, the treatment of Adenanthera pavonina galactomannan was not able to prevent the histological alterations promoted by ethanol. In the evaluation of the cicatrizing action, it was possible to observe that the ulcerated area of the group that received galactomannan from Adenanthera pavonina presented a decrease of the ulcerated area when compared to the group. In the evaluation of the intestinal transit, the treatment with the galactomannan of Adenanthera pavonina promoted a significant delay of the intestinal transit, since the tract had less extension when compared to the control group. We conclude that possibly daily supplementation with the galactomannan of Adenanthera pavonina, a source of soluble fiber, may be effective in protecting against gastric lesions and may be able to assist in the healing of already established ulcers.